Результати палеопедологічного дослідження пам’яток Малополовецького археологічного комплексу в 2007 р. - Матвіїшина, Ж.М.; Лисенко, С.Д.; Пархоменко, О.Г. (Інститут археології НАН України, 2008)
Наведено нові дані щодо реконструкції палеоландшафтів Київського Подніпров’я, отримані в 2007 р. на пам’ятках Малополовецького археологічного комплексу. В 2007 г. были продолжены палеопедологические исследования на ключевых памятниках Малополовецкого археологического комплекса — поселении Малополовецкое-2А и могильнике Малополовецкое-3. Профили почв исследовались на различных геоморфологических элементах от поймы искусственного водоема до уровня высоких террас. В катене почвы изменяются от луговых, нередко солонцеватых или солончаковатых под луговой растительностью до типичных черноземов на склонах и поверхности террас. In 2007, the palaeopedologic research continued at Malopolovetske 2A settlement and Malopolovetske 3 burial ground, the key sites of Malopolovetske archaeological complex. Soil profi les were studied on the various geomorphologic elements from the pond valley to the high terraces level. Within catena soils change from the meadow ones, often Solonetz or Solonchac with the meadow vegetation, to the typical black earth on the terraces’ slopes and surfaces.